MULTIVITAMIN EXPERIENCE IN SCHOOLCHILDREN - I.A. Gromov; R.M. Torshkhoeva (Union of pediatricians of Russia, 2008)
The article highlights the findings, pertaining to the efficiency and safety of multivitamin Pikovit forte application among children. The researchers came to conclusion that this balanced multivitamin complex is a modern high quality and low allergy medication with a pleasant flavour. It may be applied among children aged over 7 for the intense vitamin based therapy.Key words: multivitamins, children.